Perkembangan Bahasa Fonetik dan Sintaksis Anak Usia Dini (Usia 3-4 Tahun) - Sugiyanti Sugiyanti (Jurnal Kualita Pendidikan, 2021)
This study aims to analyze the language development of children at an early age of 3-4 years, by describing the development of language in the phonetic and syntactic fields of children aged 3-4 years. This research uses descriptive qualitative research method. The sample of this study were two children aged 3-4 years in KB Bustanul Janah Sambong Batang. From the two samples, it is known that the child's aspects of phonetic and syntactic development experience different developments starting from the ability to receive language, listen to other people's words, express language, enjoy listening and retell simple stories in sequence. In the aspect of phonetic language, children have developmental differences in understanding the sounds of language or how a language sound is produced by the human speech apparatus. In the aspect of syntactic language, children also have developmental differences regarding speaking and telling stories. Researchers concluded that early childhood in the age range of 3-4 years experienced differences in the development of phonetic and syntactic language. So the researchers recommend teachers to understand these differences and stimulate students according to age levels so that their development continues to increase.